65.2k views
3 votes
Help with the first section and second please. Also add explanation, or step by step. Thanks!

Help with the first section and second please. Also add explanation, or step by step-example-1

1 Answer

3 votes

1)

• 6x -2(x -5) = -2 . . . . given

• 6x -2x +10 = -2 . . . . X Cameron errored here. When multiplying -2 by -5, the result is 10, not -10.

• 4x +10 = -2 . . . . . . x terms are correctly collected

• 4x +10 -10 = -2 -10 . . . . add the opposite of the constant on the left

• 4x/4 = -12/4 . . . . divide by the x-coefficient

• x = -3 . . . . . . . . . . simplify

2)

11x -10 = -34 . . . . combine like terms

11x -10 +10 = 34 +10 . . . . addition property of equality

11x = 44 . . . . . . . . simplify

11x/11 = 44/11 . . . division property of equality

x = 4 . . . . . . . . . . . simplify

User Pablo Romeu
by
5.3k points